Are equality policies reflected in textbooks? A study in the Social Science books of Secondary Education. - Moreno Fernández, Olga; Ruiz-Alba, Pablo (IJERI: International Journal of Educational Research and Innovation, 2020)
This research has used as a technique the analysis of the content, both of the language and of the images of the textbooks that have formed part of the sample, taking as a reference the criteria of the instructions of 14 June 2018 on textbooks. The focus has been on the number of images of men and women, as well as the use of language in the three publishers studied. The sample consisted of 3 textbooks used in the Social Sciences subject (Geography and History) of the 2nd year of Compulsory Secondary Education of the publishing houses Vicens Vives, Oxford and Santillana. Use of inclusive language, 158 images analysed for category 2. Diversity, and 286 images analyzed for category 3. Social roles. The results indicate that equality policies in Andalusia aim to achieve goals that are still far from being achieved, at least in the field of education and more specifically in the values that are transmitted, so it is necessary to continue working so that equality is reflected in the textbooks present in the school classrooms.